The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/11250003.2014.911973
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and genetic divergence in island and mainland populations ofAnolis nebulosus(Squamata: Polychrotidae) from Jalisco (Mexico): an instance of insular gigantism

Abstract: The clouded anole Anolis nebulosus (Squamata: Polychrotidae) is widespread on the Pacific coast of Mexico. The species also inhabits Don Panchito, a small islet located near the coast of the Chamela-Cuixmala Biosphere Reserve in the state of Jalisco. We studied the extent of intraspecific differences in morphology (absolute size and body proportions) and in mtDNA sequences (16S and NDH2) between the population living on the islet (N = 18 for morphometry; N = 12 for mtDNA) and the one on the facing mainland (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Fitch dimorphism in A. nebulosus pooled across several populations in Mexico, and concluded that the species was the only mainland anole not However, Fitch and Hillis (1984) documented other mainland anoles that also lack sexual size dimorphism in SVL is also consistent with a previous study that found that male and female A. nebulosus growth rates in populations from Jalisco, Mexico (Siliceo-Cantero and García 2014). These results contrast with those of Senczuk et al (2014) who found that males in populations of A. nebulosus in Jalisco, Mexico were larger than females in SVL (especially in an island population), females had greater relative trunk length, and males had longer and wider heads, and there was no difference in femur length or tibia length. Jenssen (1970a) also found that male A. nebulosus were larger than females in a population from Nayarit, at least in the spring.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…Fitch dimorphism in A. nebulosus pooled across several populations in Mexico, and concluded that the species was the only mainland anole not However, Fitch and Hillis (1984) documented other mainland anoles that also lack sexual size dimorphism in SVL is also consistent with a previous study that found that male and female A. nebulosus growth rates in populations from Jalisco, Mexico (Siliceo-Cantero and García 2014). These results contrast with those of Senczuk et al (2014) who found that males in populations of A. nebulosus in Jalisco, Mexico were larger than females in SVL (especially in an island population), females had greater relative trunk length, and males had longer and wider heads, and there was no difference in femur length or tibia length. Jenssen (1970a) also found that male A. nebulosus were larger than females in a population from Nayarit, at least in the spring.…”
contrasting
confidence: 56%
“…The growth, body size, and morphology from island and mainland populations in Jalisco, Mexico have been compared (Senczuk et al 2014, SiliceoCantero andGarcía 2014, Hernández-Salinas andRamírez-Bautista in press). Some previous work found no evidence of sexual size dimorphism in A. nebulosus (Fitch 1976), whereas others found that males are larger than females (Jenssen 1970a, Senczuk et al 2014. Ramírez-Bautista and Vitt (1997) and Hernández-Salinas and Ramírez-Bautista (in press) have described the reproduction of this species from Jalisco.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Senczuk et al . () also genetically analysed San Agustín and mainland Ch‐CBR A. nebulosus and found that the island population likewise exhibited reduced genetic variation relative to the mainland. That study, which utilized only mtDNA from a smaller sample of individuals, also failed to detect haplotype sharing between island and mainland populations.…”
Section: Discussionmentioning
confidence: 97%
“…Besides the research reported here, and related work by Senczuk et al . (), Siliceo‐Cantero & Garcia () and Hernandez‐Salinas, Ramirez‐Bautista & Pavon (), only two other studies have compared the adaptive divergence of an island Anolis population with an ancestral mainland population (Klutsch et al ., ; Logan et al ., ). Both of these latter studies focused on Anolis lemurinus in the Bay Islands of Honduras, and morphological comparisons were limited to dewlap and body size.…”
Section: Introductionmentioning
confidence: 99%